High frequency of genital carriers of Leptospira sp. in sheep slaughtered in the semi-arid region of northeastern Brazil - Silva, A. F.; Farias, P. J.A.; Silva, M. L.C.R.; Araújo Júnior, J. P. [UNESP]; Malossi, C. D. [UNESP]; Ullmann, L. S. [UNESP]; Costa, D. F.; Higino, S. S.S.; Azevedo, S. S.; Alves, C. J. (Springer Nature, 2018)
Although some studies in sheep have indicated leptospire colonization of the genital tract, further studies are needed to clarify the role of genital carriers in this species. Thus, this study aimed to evaluate the colonization of pathogenic leptospires in the genital and urinary tract of slaughtered sheep. Fifty-seven adult, female woolless sheep destined for slaughter were used. Renal (n = 57), bladder (n = 57), ovary (n = 34), uterine tube (n = 44), and uterus (n = 33) samples were collected for molecular detection of Leptospira sp. DNA, and blood samples (n = 57) for serological testing. The molecular testing was performed using polymerase chain reaction (PCR), and the serological testing was performed using microscopic serum agglutination test (MAT). Samples with amplifying DNA were subjected to genetic sequencing. In total, leptospiral DNA was found in the tissues of 44 (77.2%) sheep, whereas only nine animals were positive on both PCR and MAT; there was slight agreement between PCR and MAT techniques (k = 0.0268; p = 0.684). In 61 (54.9%) genital tract and in five (4.4%) urinary tract samples, the leptospiral DNA was detected, with significant difference (p < 0.001). The genes of one sample from the uterine tube and another from the bladder were sequenced and demonstrated 99% similarity to Leptospira interrogans. Anti-Leptospira antibodies were detected in 11 (19.3%) of the tested animals. The results reinforce the importance of the genital tract as an extra-renal site of colonization, suggesting the possibility of venereal transmission in sheep.
Keywords: Genital tract; Leptospirosis; Sheep; Venereal transmission